2022
DOI: 10.3390/vaccines10040602
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Cutaneous Adverse Reaction of the AstraZeneca COVID-19 Vaccine in a Breastfed Female Infant: A Coincidence or a Rare Effect?

Abstract: The ChAdOx1 nCoV-19 vector vaccine (Vaxzevria, AstraZeneca, Cambridge, UK) was developed at Oxford University and is considered safe for the administration in lactating mothers. Nevertheless, as a novel vaccine, there are gaps in the knowledge regarding possible adverse events in breastfeeding infants of vaccinated mothers. This case report provides first-time data on a possible delayed, cutaneous, adverse reaction in a breastfed, 16-month-old female infant after the first administration of the AstraZeneca vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Even some rare cases of delayed cutaneous adverse reactions that had not been described in the AZ clinical trials were reported. [3,4] Suspected severe symptoms include thrombosis with thrombocytopenia syndrome, cerebral venous sinus thrombosis without thrombocytopenia, myocarditis, pericarditis, Guillain-Barré…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even some rare cases of delayed cutaneous adverse reactions that had not been described in the AZ clinical trials were reported. [3,4] Suspected severe symptoms include thrombosis with thrombocytopenia syndrome, cerebral venous sinus thrombosis without thrombocytopenia, myocarditis, pericarditis, Guillain-Barré…”
Section: Introductionmentioning
confidence: 99%
“…Even some rare cases of delayed cutaneous adverse reactions that had not been described in the AZ clinical trials were reported. [ 3 , 4 ] Suspected severe symptoms include thrombosis with thrombocytopenia syndrome, cerebral venous sinus thrombosis without thrombocytopenia, myocarditis, pericarditis, Guillain–Barré syndrome, idiopathic thrombocytopenic purpura, and anaphylaxis. [ 5 ] Several countries in Europe have suspended the use of the AZ vaccine owing to rare but serious conditions such as thrombosis with thrombocytopenia syndrome, and sudden death within hours or days after vaccination.…”
Section: Introductionmentioning
confidence: 99%